1958
DOI: 10.1139/b58-026
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Inorganic Elements in Marine Algae of the Atlantic Provinces of Canada

Abstract: Specimens of numerous marine species of the green, red, and brown algae from the Atlantic coast of Canada have been analyzed for total ash, Na, K, Ca, and Si, and the trace elements, As, Co, Cu, F, I, Mn, Mo, Ni, Pb, and Zn. Figures for fluorine in seaweeds are recorded for the first time. Thorough washing with tap water lowered the content of the ash, Na, K, and Si, but did not affect appreciably the concentrations of other elements.Accumulation from the sea water was apparent in greatly varying degrees in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

1970
1970
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(20 citation statements)
references
References 8 publications
2
17
0
1
Order By: Relevance
“…In the brown seaweed Fucus vesiculosus, the combined results of Black & Mitchell (1952), Young & Langille (1958) and Gutnecht (1965) have suggested that the concentration of zinc changes with that in the sea water. This was confirmed experimentally for zinc, copper and lead in Laminaria digitata, another brown weed, by Bryan (1969Bryan ( ,1971, although the relationship is not one of direct proportionality since at higher metal concentrations the concentration factor, relating the level in the weed to that in the water, is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…In the brown seaweed Fucus vesiculosus, the combined results of Black & Mitchell (1952), Young & Langille (1958) and Gutnecht (1965) have suggested that the concentration of zinc changes with that in the sea water. This was confirmed experimentally for zinc, copper and lead in Laminaria digitata, another brown weed, by Bryan (1969Bryan ( ,1971, although the relationship is not one of direct proportionality since at higher metal concentrations the concentration factor, relating the level in the weed to that in the water, is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Contents of ash, potassium, sodium, calcium in Laminaria digitata and L. longicruris from the Atlantic coast were greater in the stipes than in the fronds, however, the metallic trace elements were apparently more abundant only in the stipes of the former alga (Young and Langille, 1958). Higher ash in the stipes of N. luetkeana resulted from a disproportionately high level of potassium, however, all the other metallic elements detected were more abundant in the fronds.…”
Section: Resultsmentioning
confidence: 85%
“…A report on the calcium, phosphorus and iron concentrations in several species of the Fucaceae from the Maritime Provinces of Canada (MacPherson and Young 1952) preceded a more intensive survey of the inorganic elements present in algae of the Atlantic coast of Canada (Young and Langille 1958). As only a few elements in Nereocysiis luetkeana from the Pacific coast of Canada have been determined (Wort 1955) a more systematic examination of this alga was undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic of unspecified type has ranged from l to 15 μg g~! in a few members of the Chlorophyceae and Rhodophyceae and from 30 to 218 μg g" 1 for species of the Phaeophyceae with high levels existing in members of the Sargassaceae (Jones 1922, Williams and Whetstone 1940, Young and Langille 1958, Tagawa and Kojima 1976. Organic-bound arsenic in the oil from species of Laminaria, Fucus, Ascophyllum and Pelvetia have ranged from 5.7 to 221 μg g" 1 and from 5.0 to 36 ^g g" 1 in the corresponding total fatty acid component (Lunde 1972b).…”
Section: Introductionmentioning
confidence: 99%